Panelové sídliště Brno Bohunice - veřejný prostor a jeho udržitelnost - Spilková, Klára (Vysoké učení technické v Brně. Fakulta stavební, 2022)
Tato diplomová práce se zabývá brněnským sídlištěm Bohunice, které bylo vystavěno v letech 1972 – 1989. Konkrétně je pozornost zaměřena na veřejný prostor mezi ulicemi Moldavská a Ukrajinská. Teoretická část diplomové práce shrnuje historii panelových sídlišť od jejich vzniku až po současnost. Dále se zabývá veřejným prostorem a regenerací panelových sídlišť, popisem sídliště Bohunice a jeho stručným vývojem. Praktická část je zaměřena na urbanistickou analýzu zvoleného prostoru, na jejímž základě je vytvořen urbanistický koncept regenerace vymezeného území. Cílem návrhu je vytvoření funkčních a udržitelných veřejných prostranství v prostoru panelového sídliště Bohunice. Tato práce by se v ideálním případě mohla stát podkladem i impulsem k regeneraci veřejných prostorů sídliště Bohunice i ostatních panelových sídlišť v České republice. Cílem je představit komplexní problematiku veřejných prostor panelových sídlišť a možnosti jejich zlepšení.

This Diploma Thesis deals with the panel housing estate Brno Bohunice built in 1972 – 1989. A special attention is devoted to public space between the Moldavska and Ukrajinska streets. The theoretical part of the diploma thesis outlines the history of panel housing estates from their inception to the present. Further, it deals with public space and regeneration of panel housing estates. There follows an overview of the panel housing estate Bohunice and its brief development. The practical part focuses on an analysis of the selected area. On this basis the urban concept of regeneration of the defined area is articulated. The aim of the proposal is to create functional and sustainable public space in the area of the panel housing estate Bohunice. Ideally, this work could become a basis and impulse for the regeneration of public spaces in the Bohunice housing estate, as well as in other panel housing estates in the Czech Republic. The aim of the thesis is to outline the complex issues of public spaces of panel housing estates and the possibilities of their improvement.
The panel housing estate Brno Bohunice - public space and its sustainability
Keywords: panelové sídliště; železobeton; prefabrikace; panelová soustava; veřejný prostor; Brno; územní plán; urbanistická analýza; regenerace; udržitelnost; Bohunice; panel housing estate; reinforced concrete; prefabrication; panel system; public space; Brno; zoning plan; urban analysis; regeneration; sustainability; Bohunice